Design and Characterization of Silicone and Surfactant Based Systems for Topical Drug Delivery - Oyafuso, Marcia Helena [UNESP]; Carvalho, Flavia Chiva [UNESP]; Chiavacci, Leila Aparecida [UNESP]; Gremião, Maria Palmira Daflon [UNESP]; Chorilli, Marlus [UNESP] (Amer Scientific Publishers, 2015)
Nanotechnology offers advantages for new drug delivery design by providing drug targeting while minimizing the side effects. Polyoxyethylene 20 cetyl alcohol (CETETH-20) is a surfactant that may form nanostructured systems, such as liquid crystals, when in contact with water/oil, which are structurally similar to biological membranes and may improve skin interaction. The aim of this study was to develop and characterize CETETH 20-based nanostructured systems by combining CETETH-20 with water and different oily phases, including PEG-12-dimethicone for topical drug administration. The systems were characterized by polarized light microscopy (PLM), small-angle X-ray scattering (SAXS), rheology, texture profile analyses (TPA), in vitro cytotoxicity and histopathological analyses of rabbits' skin. Lamellar, hexagonal and cubic phases were identified and their viscoelastic moduli varied according to each phase. The stiffness of the cubic phase was 3-fold higher and twice more adhesive than the hexagonal phase. The formulations did not affect the normal macrophages cells, neither promoted skin irritation. They were spontaneously obtained by simply mixing the components, which corroborates for an ease scaled-up. These results suggest that systems composed of CETETH 20, PEG-12-dimethicone and water are a promising new approach for designing nanostructured topical drug delivery systems.
Keywords: Nanotechnology; Liquid Crystal; Microemulsion; Oleic Acid; Mineral Oil; PEG-12-Dimethicone; Brij (R); Ceteth-20